Healthcare-seeking behavior and its relating factors in South of Iran - Atefeh Khajeh; Hossein Molavi Vardanjani; Alireza Salehi; Negin Rahmani; Sajad Delavari (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Health systems aimed to increase health utilization. Habits and behavior about using health facilities, which is called health-seeking behavior, are different among different cultures and influenced by different factors. The present study is aimed at investigating Iranian Southern population health-seeking behavior and its influencing factors. MATERIALS AND METHODS: A sample of 397 people was selected using proportional stratified random sampling for this cross-sectional study. They were asked to fill a questionnaire about their health-seeking behaviors (seeking treatment, inattention to treatment, and self-medication) and socioeconomic factors. Data were analyzed using regression models including linear, ordinal, and logistic regressions. RESULTS: Near 80% of participants reported self-medication and most of them prefer public hospitals as their first point of contact with health system compared to others such as family physician. Using linear regression revealed seeking treatment has significant relationship with age (P = 0.037), living place (P = 0.018), and having complementary insurance (P = 0.013). Self-medication behavior has relation with age (P = 0.015), gender (P = 0.039), education years (P = 0.031), living place (P = 0.005), having complementary insurance (P = 0.001), and satisfaction with health-care providers (P = 0.003) in logistic regression. Using ordinal regression, it was found that inattention to treatment has a relation with education years (P = 0.044), living place (P = 0.042), having complementary insurance (P = 0.049), and severity of illness (P = 0.031). conclusion: Southern population does not accept family physician as the first point of interaction with the health system, and they prefer to go to public hospitals directly. Moreover, self-medication is a prevalent behavior among the population and thus their acceptance of health care is low. Based on the findings, it can be suggested providing more satisfying health care, increasing insurance coverage, and informing population could lead to better utilization of health-care services.